MINI-CUTTINGS ROOTING OF Sequoia sempervirens AT DIFFERENT IBA CONCENTRATIONS AND CLONES - Pereira, Mariane de Oliveira; Ângelo, Alessandro Camargo; Navroski, Marcio Carlos; de Oliveira, Luciana Magda; Felippe, Dionéia; Moraes, Carolina (Floresta, 2020)
Sequoia is a species that provides large volumes of wood, is resistant to decomposition and has seedling production by mini-cutting as a viable alternative. The aim of this work was to evaluate the rooting of mini-cuttings of different clones of Sequoia sempervirens and subsequent use of different concentrations of IBA in clones with low adventitious rooting. Mini-cuttings of different clones were used, from clonal mini-garden. In the experiment with the growth regulator, different concentrations of IBA (from 0 mg L-1 to 3000 mg L-1) were used. The material was placed to be rooted in a mini-tunnels and evaluate at 90 days. All experiments were installed in a completely randomized design, with a subsequent evaluation of survival (%), mini-cuttings with calluses (%), mini-cuttings rooted (%) and number of roots (only in the experiment with different concentrations of IBA). In the first experiment, the survival of mini-cuttings was high (close to 95%) and rooting showed great variation among the clones (22.8 to 100%). In the second experiment, using clones that previously presented rooting less than 50%, submitted to IBA application, high survival (88.1 to 99.4%) was observed. The clones presented different responses among themselves, but with improve in the rooting using growth regulator.